Prevalence, bacteriological aetiology and antibiotic susceptibility pattern of asymptomatic bacteriuria in pregnancy. - Karunaratne, K (My University, 1996)
The objective of the study was to determine the prevalence, bacteriological aetiology and antibiotic susceptibility pattern of asymptomatic bacteriuria in pregnancy, to find the correlation of the microscopic examination of the centrifuged urine deposit with standard urine culture, to determine the effect of the following host factors on the incidence of significant bacteriuria in pregnancy -age ,parity, past history of urinary tract infection (UTI),past history of catheterization and socioeconomic status The prevalence of asymptomatic bacteriuria in this study group was 3.7 per cent. Conliform organisms were found to be the most common aetiological agents in asymptomatic bacteriuria in pregnancy of which escherichia coli predominates.Gram positive bacteria plays only a small role. Nitrofurantoin could be considered as the drug of choice with a 95 per cent sensitivity.ampicillin/amoxycillin can no longer be recommended as empirical therapy due to high resistance. Pyuria detected by microscopy is a poor predictor of positive urine cultures in asymptomatic bacteriuria in pregnancy. Of the host factors evaluated only the past history of urinary tract disease showed a statistically significant correlation with the presence of bacteriuria in pregnancy. Other than this it is difficult to design a subgroup at high risk.